How important is geography for agglomeration? - Michael Roos (European Regional Science Association (ERSA), 2002)
The economic geography literature distinguishes between two types of reasons for economic agglomeration. Regional concentration of economic activity can be attributed to 'first nature' meaning geographic advantages and disadvantages given by nature or to 'second nature' meaning agglomeration economies by the interaction of economic agents. Several recent studies tried to estimate the relative importance of the two types of explanation. Most of these studies seem to exaggerate the importance of natural advantages because of loose definitions of geography. We describe geography by a small set of non-economic variables and estimate their importance for agglomeration in Germany. We find that about one third of the agglomeration of economic activity can be attributed to geography.
Keywords: 330